Luminescence of the pyrazoline dye in nanostructured zeolite matriх - Beliak, I.V.; Kravets, V.G.; Kryuchin, A.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
A physicotechnical fundamental of the multilayer photoluminescent media development has been considered. The quantum yield and relaxation time of luminescence were found as most significant values of the recording material. Organic pyrazoline dyes were adopted due to their appropriable characteristics. Possibility of the further luminescent material parameters increase while performance dye molecules in the white nanostructured zeolite matrix by components mixing and laser annealing was proposed. Experimental results with 60 % of quantum yield gain and relaxation time quadruple decrease was obtained. Using the received materials in plotting the identification luminescent elements based on the optical disc cover procedure has been determined.